2006
DOI: 10.17221/3538-pse
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spring barley genotypes with different susceptibility to Fusarium head blight using molecular markers

Abstract: 485Fusarium head blight (FHB) is a worldwide distributed cereal disease that is caused by fungi of the Fusarium genus. Infection of plants can result in yield reduction and accumulation of toxic secondary fungal metabolites, mycotoxins in kernels (Windels 2000, Takeda 2004). The number of papers dealing with FHB on barley is generally much lower than that of research studies on wheat. It is due to a much greater economic importance of wheat as a cereal crop, but as well as to the fact that FHB causes larger ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In barley, the assessment of a disease according to symptoms and other measurements is even more complicated than in wheat. Insignificant correlations were found out by Nesvadba et al (2006) between ear infection percentage and DON content and also between the percentage of fusaria in a laboratory test and DON content. By contrast, other authors (Urrea et al 2002;Buerstmayr The objective of this paper was to present results of artificially inoculated field experiments in which 44 spring barley cultivars were examined over two years for the accumulation of the mycotoxin DON in grain and the important FHB severity traits to investigate genetic variation in these traits and to identify possible new sources for resistance breeding.…”
mentioning
confidence: 94%
“…In barley, the assessment of a disease according to symptoms and other measurements is even more complicated than in wheat. Insignificant correlations were found out by Nesvadba et al (2006) between ear infection percentage and DON content and also between the percentage of fusaria in a laboratory test and DON content. By contrast, other authors (Urrea et al 2002;Buerstmayr The objective of this paper was to present results of artificially inoculated field experiments in which 44 spring barley cultivars were examined over two years for the accumulation of the mycotoxin DON in grain and the important FHB severity traits to investigate genetic variation in these traits and to identify possible new sources for resistance breeding.…”
mentioning
confidence: 94%
“…(Bérubé et al 2012;Salas et al 1999;Schöneberg et al 2016;Tekauz et al 2000). However, in other studies, no correlation between presence of DON and disease severity (Nesvadba et al 2006), visually infected kernels (Tekauz et al 2000), a decrease in kernel weight (Tekauz et al 2000) or presence of Fusarium spp. (Abramson et al 1998;Xue et al 2006) was found.…”
Section: Correlation Between Symptoms Of Fusarium Infection and Mycot...mentioning
confidence: 85%
“…However, other studies could not find such a correlation between disease severity and presence of Fusarium spp. (Nesvadba et al 2006;Tekauz et al 2000) or visually infected kernels (Tekauz et al 2000). In some studies, presence of DON was correlated to the disease severity (Berger et al 2014;Buerstmayr et al 2004;Chrpová et al 2011;Legzdina and Buerstmayr 2004;Salas et al 1999;Thin et al 2004), visually infected kernels (Berger et al 2014;Legzdina and Buerstmayr 2004), a decrease in kernel weight (Chrpová et al 2011) or presence of Fusarium spp.…”
Section: Correlation Between Symptoms Of Fusarium Infection and Mycot...mentioning
confidence: 99%
See 1 more Smart Citation